2022
DOI: 10.1007/s10639-022-11071-y
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of education and information technologies: Insights from a topic modeling based bibliometric analysis

Abstract: Education and Information Technologies (EAIT) has been a leading journal in education & educational research since 1996. To celebrate its 25th anniversary and provide a comprehensive overview of the field, a topic modeling-based bibliometric analysis was conducted on the articles published in this journal. The study is constructed upon two methods, bibliometric analysis, and topic modeling. The study aims to find out the trends in publications and citations, prominent countries, affiliations and the status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 59 publications
0
18
1
Order By: Relevance
“…The seven topics found in this study were not aligned with previous literature reviews on educational technology (e.g., Chen et al, 2020 ; Ozyurt & Ayaz, 2022 ; Tatnall & Fluck, 2022 ). In a study examining research trends of BJET , Chen et al ( 2020 ) identified 15 topics relating to a teacher (e.g., teacher education), learning strategies (e.g., problem-based learning, game-based learning, mobile-assisted language learning, socialized e-learning), learning environment (e.g., online social communities), evaluation (assessment and feedback), and other areas (e.g., early childhood education in the digital age and review studies).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The seven topics found in this study were not aligned with previous literature reviews on educational technology (e.g., Chen et al, 2020 ; Ozyurt & Ayaz, 2022 ; Tatnall & Fluck, 2022 ). In a study examining research trends of BJET , Chen et al ( 2020 ) identified 15 topics relating to a teacher (e.g., teacher education), learning strategies (e.g., problem-based learning, game-based learning, mobile-assisted language learning, socialized e-learning), learning environment (e.g., online social communities), evaluation (assessment and feedback), and other areas (e.g., early childhood education in the digital age and review studies).…”
Section: Discussioncontrasting
confidence: 94%
“…Since 2000, researchers studying educational technologies have become more concerned with new learning strategies with emerging technologies that could enhance student collaboration and autonomy, such as e-learning, mobile and blended learning, and social network-based learning (Ozyurt & Ayaz, 2022 ; Tatnall & Fluck, 2022 ). These topics, however, were not identified in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be inferred that the terms "gamification", "higher education", "motivation", "game-based learning", "education", and "e-learning" have greater impact, suggesting the hot topics of gamification research in higher education. In brief, it indicates that this topic has gained an important place among educational technology researchers in the last decade [50]. The author keywords are considered essential to analyze in the current study due to the fact that the keywords of an author generally represent the content of the paper [51].…”
Section: Discussionmentioning
confidence: 99%